2014
DOI: 10.14233/ajchem.2014.17087
|View full text |Cite
|
Sign up to set email alerts
|

A New Triterpene Glycoside from Fagonia cretica

Abstract: INTRODUCTIONFagonia cretica L. is a well-known desert medicinal plant which belongs to the family Zygophyllaceae. It is a small annual herb with woody branches. Fagonia is a genus of 34 species confined to warm areas of all continents except Australia. F. cretica is reputed to be a medicinal plant in scientific and folkloric literature and its medicinal values are well documented. An aqueous decoction of the aerial parts of the plant is the popular remedy in the indigenous system of medicine for cancer in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…Methanolic extracts of F. cretica have good antimicrobial potential as well as strong antioxidant activity against reactive oxygen and nitrogen species. Our study also found strong antioxidant activity 18,19 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Methanolic extracts of F. cretica have good antimicrobial potential as well as strong antioxidant activity against reactive oxygen and nitrogen species. Our study also found strong antioxidant activity 18,19 .…”
Section: Discussionsupporting
confidence: 79%
“…Secondary metabolites are used for checking biological activities such as antioxidant activity 16,17 . Methanolic solvent extracts of F. cretica has good antimicrobial activity as well as strong antioxidant activity against reactive radical species 18,19 .…”
Section: Research Articlementioning
confidence: 99%
“…Moreover 3-O-β-Dglucopyranosyl-Hederagenin (10) was isolated from the aerial part of F.cretica [39] . The isolation of a new Triterpene glycoside;3-β-O-[(6-deoxyα-L-talopyranosyl)oxy]-22-α-hydroxyurs-12-en-28-oic acid (fagonoside A) (11) from the whole plant of F. cretica has been recognized by Anjum et al [50] . Further study revealed that other four Triterpenoid Saponins were also isolated from F. cretica aerial parts and identified as a new compounds.…”
Section: Saponinsmentioning
confidence: 99%
“…A total of forty-nine triterpenoid saponins (1-49) have been identified in the five investigated Fagonia species, F. arabica L. (Miyase et al, 1996a;Shoeb et al, 1994;Perrone et al, 2007), F. cretica L. (Abdel Khalik et al, 2000aBatterjee et al, 2002;Anjum et al, 2014;Saleem et al, 2014), F. glutinosa Delile (Melek et al, 2000), F. indica Burm.f. (Ansari et al, 1987(Ansari et al, , 1988Shaker et al, 1999Shaker et al, , 2000Shaker et al, , 2013Farheen et al, 2015), and F. mollis Delile (Sallam et al, 2014).…”
Section: Previous Workmentioning
confidence: 99%
“…The hydroxyl in C-3 position was also glycosylated by a β-D-glucopyranosyl unit (2, 6-7, 10, 45-47) or by an α-L-arabinopyranosyl which can be substituted in C-2 and/or C-3 positions by a β-D-glucopyranosyl and/or a β-D-xylopyranosyl units (11-32, 35-40, 43-44).Saponins isolated from Fagonia cretica(Batterjee et al, 2002) were slightly different with an α-L-rhamnopyranosyl substituted in C-4 position by a β-D-glucopyranosyl unit (33) or a disaccharide moiety (β-D-glucopyranosyl-(1→5)-α-L-arabinofuranosyl) (34). In fagonoside A (49) isolated from F. cretica(Anjum et al, 2014) a 6-deoxy-α-L-talopyranosyl was attached to the 3β,22α-dihydroxyurs-12-en-28-oic acid. Sulfated saponins were described in F. arabica(Perrone et al 2007) (3-4, 8-9, 22-23), F. indica(Shaker et al, 1999) (43-44), and F. mollis…”
mentioning
confidence: 99%